2023
DOI: 10.1002/fsn3.3580
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of different processing methods on the selected nutritional properties of pumpkin and determining the appropriate process for pumpkin yogurt

Abstract: The processing methods, especially cooking, can cause quality losses, particularly in the nutritional value of the fresh product. This study investigated the effects of preprocessing methods on the nutritional properties of pumpkin and the physicochemical and sensory properties of pumpkin yogurt. Two different pumpkin varieties (Cucurbita pepo and Cucurbita maxima) were subjected to three different preprocessing methods (freeze‐drying, boiling, and baking). Boiling significantly increased antioxidant activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Sıçramaz and Ayar ( 2023 ) determined the influence of various pre‐processing methods on the nutritional properties of two pumpkin varieties, Cucurbita pepo and C. maxima . The TPC and AA of the freeze‐dried C. maxima fruits were 244.5 mg GAE and 501.2 μmol TE per 100 g dm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sıçramaz and Ayar ( 2023 ) determined the influence of various pre‐processing methods on the nutritional properties of two pumpkin varieties, Cucurbita pepo and C. maxima . The TPC and AA of the freeze‐dried C. maxima fruits were 244.5 mg GAE and 501.2 μmol TE per 100 g dm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, this amount can vary depending on factors like the variety of pumpkin and its growing conditions. Sıçramaz and Ayar ( 2023 ) reported that freeze‐dried fruits from the C. pepo and C. maxima varieties had calcium contents of about 6 g per 100 g dm and reduced significantly for the former variety after baking. This reduction could be attributed to the release of water from plant tissues during heat treatment.…”
Section: Resultsmentioning
confidence: 99%